Evaluating Economic Resilience: Lighting the Nexus Between Turkish Imports and Foreign Exchange Reserves - Tekin Bilgehan (Studies in Business and Economics)
This study investigates the relationship between Türkiye’s imports and foreign exchange reserves, aiming to provide detailed information about Türkiye’s economic dynamics by using data from October 2002 to July 2022 and several robust methodologies, including ARDL Bound tests, Johansen co-integration tests, FMOLS, DMOLS and VECM Granger. The findings reveal a stable long-term balance between imports and foreign exchange reserves and a bidirectional causality that enriches the understanding of the dynamic interaction. This study advances the academic discourse on Türkiye’s economic resilience and provides valuable information to policymakers navigating the complex landscape of import-reserve dynamics in Türkiye.